Evaluating the effect of Roxadustat on ventricular repolarization in patients undergoing peritoneal dialysis - Yangyang Zhang; Liang Zhang; Pengcheng Ge; Ruyi Xu; Zhen Ye (European Journal of Medical Research, 2023)
Abstract Background Roxadustat is a novel oral medication used to treat anemia in CKD patients. Several studies have shown that Roxadustat can alleviate anemia in CKD patients by increasing hemoglobin levels and regulating iron metabolism. We aimed to evaluate the effect of Roxadustat on ventricular repolarization in PD patients. This study may provide a new integrated approach to the assessment and treatment of CKD. Methods The present prospective cohort study enrolled 65 CKD patients who were treated with Roxadustat and 31 CKD patients who received conventional therapy between January 2021 and June 2022. All patients were examined for ECG in the absence of clinical symptoms and compared the ECG indicators. Demographic and clinical data of all patients were collected. All data used SPSS 18.0 for statistical analyses. Results The T peak-to-end (Tpe) of PD patients in the Roxadustat group was remarkably slower than that of patients in the conventional group. Additionally, the Tpe/QT ratio in the conventional group was significantly elevated than that in the Roxadustat group. The results of logistic regression analysis showed that Tpe (95%CI 1.191 ~ 2.141, P = 0.002) and Roxadustat treatment (95%CI 1.357 ~ 42.121, P = 0.021) were the risk factors of PD patients with high Tp-e/QT ratio. Conclusion In summary, we found that Roxadustat could improve ventricular repolarization in peritoneal dialysis patients, which indicated a potential cardiovascular protective effect of Roxadustat. This study might provide a new integrated approach to the assessment and treatment of CKD.